Control de cortadera (Scleria pterota Presl.) y establecimiento de pasto - Argel M., Pedro J.; Doll, Jerry D. (1975)
Cutting sedge (Scleria pterota Presl.) is a common weed in pastures. It grows vigorously and forms patches in poorly drained soils and appears uniformly dispursed in pastures on rolling land. It is unpalatable to cattle and is extremely competitive with pasture species. It was found that both diuron at 2 or 3 percent plus 0.5 percent surfactant and glyphosate at 1 or 2 percent killed the sedge in the rainy season. Diuron gave the best control when rain fell immediately after application but rain greatly reduced glyphosate`s effectiveness. The pasture grasses pará and angleton were established in a separate trial 25 days after appling glyphosate or diuron. Pará was established succesfully and covered 90 percent of the soil surface four months after vegetative seeding. Angleton did not establish either by sexual seed or by stolones due to high soil moisture and the residual effect of diuron on the seeds.